Операторные методы в задаче оценки асимптотики момента первого достижения для процесса рождения и гибели - Мажуга, Ю.И. (Український математичний журнал, 1993)
Estimates are established for the exponential asymptotics of the time of the first hit of a certain leveln for the birth and death process.